Wastewater reuse for irrigation- salinity issues on coastal cities - Kathijotes, Nicholas (My University, 2010)
The continuous global population growth increases the demand for water which, in arid and semi arid regions like the Mediterranean and the Balkans is considered as a limited resource. Future demands will not be met by traditional water resources like surface and ground water. In order therefore to handle increased water demand, the treated wastewater originating from municipal wastewater treatment plants has to be developed and offered to farmers for agricultural irrigation. Since public health is an important aspect in wastewater reuse, this study was carried in order to investigate the difficulties resulting from the degraded quality of treated sewage on humans and the environment as well its public acceptance. Its effects on soils were investigated by investigating wastewater-irrigated areas in terms of profile investigations and comparing the results to similar profiles irrigated with groundwater. Treated wastewater qualities were also investigated by carrying a complete risk assessment. Public acceptance faces serious problems and therefore its real effects on humans and plants were examined with emphasis on known research in Cyprus. Salinity is a major wastewater reuse problem, especially in coastal cities like Larnaca in Cyprus, and is investigated. Results suggest that problems could become very serious if corrective measures are not taken. Proper salinity management methods are suggested.

The continuous global population growth increases the demand for water which, in arid and semi arid regions like the Mediterranean and the Balkans is considered as a limited resource. Future demands will not be met by traditional water resources like surface and ground water. In order therefore to handle increased water demand, the treated wastewater originating from municipal wastewater treatment plants has to be developed and offered to farmers for agricultural irrigation. Since public health is an important aspect in wastewater reuse, this study was carried in order to investigate the difficulties resulting from the degraded quality of treated sewage on humans and the environment as well its public acceptance. Its effects on soils were investigated by investigating wastewater-irrigated areas in terms of profile investigations and comparing the results to similar profiles irrigated with groundwater. Treated wastewater qualities were also investigated by carrying a complete risk assessment. Public acceptance faces serious problems and therefore its real effects on humans and plants were examined with emphasis on known research in Cyprus. Salinity is a major wastewater reuse problem, especially in coastal cities like Larnaca in Cyprus, and is investigated. Results suggest that problems could become very serious if corrective measures are not taken. Proper salinity management methods are suggested.
Keywords: Wastewater; Wastewater reuse; Salinity; SAR; Irrigation; Wastewater; Wastewater reuse; Salinity; SAR; Irrigation